Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae) - Komai, Tomoyuki; Matsuzaki, Koji (Zootaxa, 2016)
Two species of decapod crustaceans collected from deep sea off eastern Hokkaido, Japan, are reported. Sclerocrangon rex n. sp. (Caridea: Crangonidae) is described and illustrated on the basis of material collected off Kushiro and in the Nemuro Strait at depths of 500–1000 m. It is morphologically similar to S. derjugini Kobjakova, 1936 and S. igarashii Komai & Amaoka, 1991, both occurring in waters off eastern Hokkaido, but is easily distinguished from the latter two by the possession of an extra spine on the postorbital carina on the carapace, located posterior to the level of hepatic spines. The second, Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae), is the first representative of this squat lobster family to be recorded from northern Japan. The single specimen of M. verrilli was collected in the Nemuro Strait off Shiretoko Peninsula at depths of 700–1000 m.